Development of Learning Media Through Bookwidgets for A1 Vocabulary - Amanda Putri Ayu Gayatri; Hafniati, Hafniati (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to create learning media with the help of Bookwidgets for A1 level vocabulary. This research is a development research, the method used in this study is qualitative descriptive and uses Richey and Klein's theory, which consists of three phases, namely: 1) planning, 2) production, 3) evaluation. The data of this research was obtained from the vocabulary on the theme, Guten Appetit